Vascular Dysfunction in Preeclampsia. (January 2014) - Brennan, Lesley J.; Morton, Jude S.; Davidge, Sandra T.
Abstract Preeclampsia is a complex disorder which affects an estimated 5% of all pregnancies worldwide. It is diagnosed by hypertension in the presence of proteinuria after the 20th week of pregnancy and is a prominent cause of maternal morbidity and mortality. As delivery is currently the only known treatment, preeclampsia is also a leading cause of preterm delivery. Preeclampsia is associated with maternal vascular dysfunction, leading to serious cardiovascular risk both during and following pregnancy. Endothelial dysfunction, resulting in increased peripheral resistance, is an integral part of the maternal syndrome. While the cause of preeclampsia remains unknown, placental ischemia resulting from aberrant placentation is a fundamental characteristic of the disorder. Poor placentation is believed to stimulate the release of a number of factors including pro‐ and antiangiogenic factors and inflammatory activators into the maternal systemic circulation. These factors are critical mediators of vascular function and impact the endothelium in distinctive ways, including enhanced endothelial oxidative stress. The mechanisms of action and the consequences on the maternal vasculature will be discussed in this review.